Cambodia : Teacher Policies - World Bank (Washington, DC, 2014)
Research suggests that teacher quality is the main school-based predictor of student achievement and that several consecutive years of outstanding teaching can offset the learning deficits of disadvantaged students (Hanushek and Rivkin, 2006; Nye et al, 2004; Park and Hannum, 2001; Rivkin et al, 2005; Rockoff, 2004; Sanders, 1998; Sanders and Rivers 1996; and Vignoles et al, 2000). However, it is not yet clear exactly which teacher policies can raise teacher effectiveness (Goldhaber, 2002 and Rivkin et al, 2005). Thus, devising effective policies to improve teaching quality remains a challenge. There is increasing interest across the globe to attract, retain, develop and motivate great teachers. While the World Bank has ample experience in supporting teacher policy reforms in developing countries, until recently there was no systematic effort to offer data and analysis that can provide policy guidance on teacher policies. The focus of the initiative is the design of teacher policies as opposed to their implementation on the ground. A number of complementary activities will be looking at implementation in a sample of countries as this will involve a different methodological approach and will require more financial and human resources.